Comparison of endoscopic variceal ligation and beta-blocker (carvedilol) plus nitrate for the primary prevention of variceal bleeding - Singh Yadav, Anilesh Kumar; B. P., Priyadarshi; A. C., Gupta; Singh, Mahendra; Verma, Ashok Kumar; Gupta, Vishal (International Journal of Advances in Medicine, 2017)
Background: Esophageal variceal bleed is a major problem in patients with cirrhosis. Endoscopic sclerotherapy and variceal ligation are effective in stopping bleeding in up to 90% of patients. Beta-blocker (Carvedilol) + Isosorbide Mononitrate are promising alternative to other nonselective beta blocker or endoscopic band ligation for the prevention of first variceal bleeding of medium to large varices, which needs to be further explored. Methods: The present study was an observational study in 200 patients at LLR and Associated Hospitals PG Department of Medicine GSVM Medical College, Kanpur. After randomization 120 patients underwent for Endoscopic Variceal ligation and 80 patients were put on beta-blocker (Carvedilol) + Isosorbide Mononitrate therapy for the primary prevention of variceal bleeding. Results: Most common cause of portal hypertension was liver cirrhosis (in carvedilol plus isosorbide mononitrate group 70%, and it was 85%. in EVL group. Bleeding in patients of carvedilol plus isosorbide mononitrate was significantly lower (23.75%) than patients of EVL (60%) group. Reduction in bleeding was statistically highly significant (p value < 0.05). Mortality among patients receiving combination therapy with carvedilol plus isosorbide mononitrate was (12.5%) comparison to EVL (21.66%). Reduction in mortality was statistically not significant. (p value >0.05). Adverse effects were significantly lower among patients receiving combination therapy with carvedilol plus isosorbide mononitrate (38.75%) than patients of EVL (86.66%) group. Conclusions: Both EVL and beta-blockers may be considered first-line treatment to prevent first variceal bleeding, whereas beta-blockers (carvedilol) plus isosorbide mononitrate may be the best choice for the prevention of re-bleeding.